2017
DOI: 10.1002/smr.1882
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the relationship between project productivity and environment factors in the use case points method

Abstract: Project productivity is a key factor for producing effort estimates from use case points (UCP), especially when the historical dataset is absent. The first versions of UCP effort estimation models used a fixed number or very limited numbers of productivity ratios for all new projects.These approaches have not been well examined over a large number of projects, so the validity of these studies was a matter for criticism. The newly available large software datasets allow us to perform further research on the use… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 34 publications
2
23
0
Order By: Relevance
“…The IFPUG method provides complexity measurements, (size), only. If a software development effort -(time in person-hours), is needed; a productivity factor (PF) has to be used to obtain the number of personhours [10]. The proposed CVS model can be used for the estimation of the software development effort in person-hours.…”
Section: Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…The IFPUG method provides complexity measurements, (size), only. If a software development effort -(time in person-hours), is needed; a productivity factor (PF) has to be used to obtain the number of personhours [10]. The proposed CVS model can be used for the estimation of the software development effort in person-hours.…”
Section: Problem Statementmentioning
confidence: 99%
“…The original IFPUG method leads to complexity measurements, (size). If a software development effort -(time in person-hours) is needed, then a Productivity Factor (PF), has to be used for the transformation of the estimated size into the number of person-hours [10].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the use of the subset selection method could improve the level of predictive accuracy. 12 The study that examines other UCP elements, namely, productivity projects was carried out by Azzeh and Nassif 13 who examined the relationship between productivity of project and environment factors (EFs) in UCP in which project productivity is a key factor to obtain estimation effort.…”
Section: Related Workmentioning
confidence: 99%
“…Other researchers called ER with the term productivity factor (PF) 10 or project productivity, 13,15 others call it person-hours. 30 The ER value is set equal to 20 man-hours/UCP.…”
mentioning
confidence: 99%
“…Then the productivity and UCP are used within a log‐linear regression model to calculate the software effort. Azzeh et al studied and investigated the relationship between environmental factors and productivity. They found that the environmental factors can work as good indicator for productivity prediction when historical data are available.…”
Section: Related Workmentioning
confidence: 99%